Case reportPachydermoperiostosis – Touraine-Solente-Gole syndrome (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Pachydermoperiostosis is a rare idiopathic hypertophic osteoarthropathy with unknown etiology. Pathological lesions involve both skin and the skeletal system. Literature data concerning symptoms, histopathological changes and possible triggering factors of this pathological entity were reviewed.